Phased-array radar design application of radar fundamentals - Jeffrey, Tom 1954- (SciTech Publishing, 2009)
The following topics are discussed in this book: radar target detection; radar tracking; matched filtering; radar signal processing; search radar; data association; target classification; phased array radar; interference suppression; missile defense radar design; early warning radar design; and air defense radar design.